A study on clinical patterns of nonvenereal male genital dermatoses at a rural-based tertiary care center - Rochit R Singhal; Pragya Ashok Nair (Wolters Kluwer Medknow Publications, 2021)
Background: All dermatoses affecting genitalia are not sexually transmitted. Wrongly labeling a patient as a case of venereal disease can have great psychosocial implications, apart from the resultant wrong treatment. It is necessary to have detailed knowledge and broader view while approaching genital lesions as it can be a nonvenereal disease. Objectives: The aim was to study the clinical patterns of nonvenereal male genital dermatoses. Materials and Methods: It was a cross-sectional observational study of male patients having nonvenereal genital dermatoses attending the Department of Dermatology for a period of 1 year from June 2016 to May 2017. Male patients with genital lesions were included in the study after taking their written consent in vernacular language. A detailed history and examination was carried out according to a prestructured pro forma. Investigations were done as and when required. Patients diagnosed with sexually transmitted disease were excluded from the study. Results: The study included 200 male patients having forty different nonvenereal genital dermatoses. Most patients belong to the age group of 19-40 years (46%), with a mean age of 36.47 years. Most of them were students (32%), were graduate (38.5%), and belonged to middle socioeconomic class (60.5%). Sixty percent of the patients were married. Common dermatoses encountered were scabies (27 [13.5%]), dermatophytoses (19 [9.5%]), scrotal dermatitis (16 [8%]), lichen planus (15 [7.5%]), vitiligo (12 [6%]), and psoriasis and pearly penile papules each with 10 (5%) cases. Other rare dermatoses were median raphe cyst, genital lentigenosis, granuloma annulare, nevus, cutaneous tuberculosis, and lichen sclerosus. Conclusions: Scabies was the most common nonvenereal genital dermatosis found in this study.